2016
DOI: 10.11118/actaun201664041149
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Quality Milking Process By Thermographic Method

Abstract: The aim of the study was to determine the milking process quality through the temperature changes on teats. The measurements were conducted to evaluate the effect of partial vacuum 45 kPa and 40 kPa at the mammary gland. The measurements were done on a dairy farm at six Holstein breed dairy cows that were in the second stage of lactation. Temperature changes on teats were measured with thermal camera ThermoProTM TP8S IR during 2 days (morning milking and afternoon milking partial vacuum to 45 kPa, morning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…Results are consistent with studies of foreign scientists (Berry et al, 2003;Paulrud et al, 2005). Total difference between the teat temperature before washing and after milking was lower than results provided by Hanusová et al (2016). It was probably caused by higher temperature in stable.…”
Section: Unauthenticatedcontrasting
confidence: 58%
“…Results are consistent with studies of foreign scientists (Berry et al, 2003;Paulrud et al, 2005). Total difference between the teat temperature before washing and after milking was lower than results provided by Hanusová et al (2016). It was probably caused by higher temperature in stable.…”
Section: Unauthenticatedcontrasting
confidence: 58%
“…The use of lower vacuum pressure (40 kPa) in the present experiment may have been one of the causes of no increase in temperature of the teats after milking. Hanusová et al (2016) reported an increase in the temperature of teats after milking, of approximately 2.0°C, even at 40 kPa pressure. This result may be related to the difference in breed and age of cows evaluated (primiparous Girolando vs. multiparous Holstein cows).…”
Section: Discussionmentioning
confidence: 97%
“…Hanusová et al . (2016) reported an increase in the temperature of teats after milking, of approximately 2.0°C, even at 40 kPa pressure. This result may be related to the difference in breed and age of cows evaluated (primiparous Girolando vs. multiparous Holstein cows).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the teat SST did not assume its initial values until three minutes after milking and no visible teat injuries were caused by any of the liners investigated. In the study by Junga et al (2016) on the udder and teat SST in 19 dairy cows, it was found that machine milking (2 × 2 Westfalia tandem milking machine) caused a significant increase in the SST of both front and rear udder teats but not in the SST of the udder quarters, whereas Hanusová et al (2016) analyzing the effect of two different partial vacuum levels (45 kPa and 40 kPa) on teat SST in six Holstein cows (bucket milking system) found that both levels increased the SST values immediately after milking (by 2.44 and 1.93 K, respectively) and that the increase after afternoon milking was significant, while that after morning milking was not.…”
Section: Discussionmentioning
confidence: 99%